2020
DOI: 10.1177/0954405420970517
|View full text |Cite
|
Sign up to set email alerts
|

An integrated machine learning: Utility theory framework for real-time predictive maintenance in pumping systems

Abstract: Bearings are the most widely used mechanical parts in rotating machinery under high load and high rotational speeds. Operating continuously under such harsh conditions, wear and failure are imminent. Developing defects give rise to even-higher vibration and temperature levels. In general, mechanical defects in a machine cause high vibration levels. Therefore, bearing fault identification and early detection enables the maintenance team to repair the problem before it triggers catastrophic failure in the bearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…e output (prediction) is the quality check in lubrication and cooling machining environments. By performing the different models, we should find absolute error percentage, maximum absolute error, mean fundamental error, root square error, and correlation coefficient with practically observed values [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…e output (prediction) is the quality check in lubrication and cooling machining environments. By performing the different models, we should find absolute error percentage, maximum absolute error, mean fundamental error, root square error, and correlation coefficient with practically observed values [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Their results indicated that XGBoost is capable of monitoring a ship's main engine system quickly and accurately, thus reducing the maintenance and operating cost and improving the availability rate [15]. The researchers pointed out that the integrated learning algorithm achieves better results regarding machine failure and early warnings [16,17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Statistical Process Control (SPC) 14 is the typical tool, as proposed by Liu et al 15 and Colosimo et al 16 Diagnosis is a classification problem. Several types of algorithms could be used to localise and identify the nature of the fault: Linear Discriminant Analysis (LDA), Support Vector Machines (SVM), 17 Mahalanobis-Taguchi Systems, 18 filtering techniques, for example, Unscented Kalman Filter (UKF) 19 and Artificial Neural Networks (ANN) are just a subset of possible solutions. 11,20,21 An innovation in this field could be progressive learning, introducing the capability of increasing the number of clusters during online learning.…”
Section: Introductionmentioning
confidence: 99%
“…It was successfully implemented to support decision making in maintenance actions on bearing faults in a sewage treatment plant. 17 Dealing with prognostics, four main algorithm categories can be distinguished depending on the data availability and the approach to the problem 10,23 : Knowledge-based models: expert knowledge is translated in simple rules that the system can interpret. Such methods can be used only if robust knowledge of the degradation phenomenon and the machine is available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation